2021
DOI: 10.1177/19458924211032469
|View full text |Cite
|
Sign up to set email alerts
|

Is Body Mass Index Related to Skin Reactivity to Histamine but not to Specific Allergens? A 2-Year Follow-up Study on Korean Children

Abstract: Background Skin prick tests are widely used to diagnose allergic sensitization. The influence of obesity on the skin prick test result has not been clearly established, even though the association between allergic disease and obesity is relatively well known. Objective To determine whether a change in body mass index (BMI) contributes to skin reactivity to histamine and allergens in a skin prick test, we performed a 2-year follow-up study on Korean children. Methods Skin prick tests for common aeroallergens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Histamine is the main proin ammatory mediator that accounts for at least half of the signs and symptoms of AC [29]. Clinical studies have found that an increased histamine reaction is associated with increased BMI [27,30]. Furthermore, obesity may enhance in ammation in AR and BA [31,32].…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histamine is the main proin ammatory mediator that accounts for at least half of the signs and symptoms of AC [29]. Clinical studies have found that an increased histamine reaction is associated with increased BMI [27,30]. Furthermore, obesity may enhance in ammation in AR and BA [31,32].…”
Section: Risk Factorsmentioning
confidence: 99%
“…The increase in the number of obese children has coincided with an increase in the incidence of allergies, which clinically manifest as chronic respiratory diseases (asthma, AR, AD) [25]. Many prospective studies have veri ed that obesity/high BMI is a risk factor for the development of atopic allergic diseases, such as AD, AR and BA [26,27]. However, there are few reports on the relationship between BMI and AC incidence.…”
Section: Risk Factorsmentioning
confidence: 99%
“…6 It is incredible to think that over the past 30 years, the safety of general anesthesia has increased almost 60-fold, and Levi et al, examine whether pushing the age boundaries of elective anesthesia for endoscopic sinus surgery aligns with that trend-a point of importance for the large segment of our aging population. 7 It is also curious to see how comorbidities affect nonsurgical outcomes as Suh et al, examines BMI as it relates to histamine response 8 , and Amarbir et al, examine the functional comorbidity index and its relation to chronic rhinosinusitis. 9 Similarly incredible is the revolution biological therapies and immunomodulators have created in the treatment of sinusitis, asthma, and other ectopic diseases.…”
mentioning
confidence: 99%